2020
DOI: 10.1186/s13075-020-02276-y
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of genome-wide association study identifies FBN2 as a novel locus associated with systemic lupus erythematosus in Thai population

Abstract: Background: Differences in the expression of variants across ethnic groups in the systemic lupus erythematosus (SLE) patients have been well documented. However, the genetic architecture in the Thai population has not been thoroughly examined. In this study, we carried out genome-wide association study (GWAS) in the Thai population. Methods: Two GWAS cohorts were independently collected and genotyped: discovery dataset (487 SLE cases and 1606 healthy controls) and replication dataset (405 SLE cases and 1590 un… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 71 publications
0
6
0
2
Order By: Relevance
“…To identify the SLE causal variants in the enhancers of IRF5, we first collected all SLE risk variants at IRF5 locus (GWAS catalog variants and the variants that have been reported to affect IRF5 expression in SLE patients) (2,5,14,16,17,(27)(28)(29)(30)(31)(32)(33)(34)(35). Next, we used the SCREEN system (https://screen.encodeproject.org/), a tool for searching candidate cis-regulatory elements derived from Encyclopedia of DNA Elements (ENCODE) data, to analyze the enhancer characters of these single-nucleotide polymorphisms (SNPs) (36).…”
Section: Resultsmentioning
confidence: 99%
“…To identify the SLE causal variants in the enhancers of IRF5, we first collected all SLE risk variants at IRF5 locus (GWAS catalog variants and the variants that have been reported to affect IRF5 expression in SLE patients) (2,5,14,16,17,(27)(28)(29)(30)(31)(32)(33)(34)(35). Next, we used the SCREEN system (https://screen.encodeproject.org/), a tool for searching candidate cis-regulatory elements derived from Encyclopedia of DNA Elements (ENCODE) data, to analyze the enhancer characters of these single-nucleotide polymorphisms (SNPs) (36).…”
Section: Resultsmentioning
confidence: 99%
“…Lupus Eritematoso Sistémico es el nombre otorgado a una enfermedad autoinmune que provoca inflamación crónica, pérdida de tolerancia a antígenos propios y además de una activación inmune inadecuada con afectación multisistémica como el caso de: piel, riñón o cerebro y de presentación clínica muy heterogénea que va desde manifestaciones cutáneas leves hasta el fallo orgánico, (2)(3)(4)(5)(6)(7)(14)(15)(16) su patogénesis está relacionada con la susceptibilidad genética del individuo en conjunto con factores ambientales, entre estos tenemos: luz ultravioleta, infecciones virales y bacterianas, consumo de alcohol o tabaco, deficiencia de vitamina D, algunos químicos ocupacionales y no ocupacionales, los niveles hormonales, considera la mala supresión de las células B y el exceso de células T como mediadores importantes en el desarrollo de esta enfermedad, en donde la pérdida de la tolerancia inmune evita la respuesta humoral y celular hacia autoantígenos; la tolerancia inmune se define como el estado no responsivo a moléculas que podrían causar una reacción inmune evitando así, que se ataque a sus propios antígenos mediante mecanismos de tolerancia centrales y periféricos. (2,9,10,15,17) Esta patología se presenta mayoritariamente en mujeres teniendo un rango de relación de 8:1 a 15:1 si se compara con el sexo masculino; se ha observado asociación a genes de cromosomas sexuales, hormonas sexuales, la estabilidad de la microbiota intestinal, etc, pues la mayor prevalencia se ha determinado en las etapas de pre-pubertad y posmenopausia; (2) al ser más evidente durante la edad reproductiva comprende un reto médico y psicológico a la hora de tratar un embarazo o en su defecto planificación familiar; una de las características que resulta en una mayor posibilidad de presentar esta patología es, la etnia, puesto que se ha denotado un incremento en la severidad y prevalencia en mujeres afrodescendientes, asiáticas e hispanas en una relación 4:2 si se compara con aquellas mujeres blancas.…”
Section: Lupus Eritematoso Sistémicounclassified
“…(1) Dentro de este contexto, el lupus eritematoso sistémico (LES) o (SLE) por sus siglas en inglés, constituye una patología de etiología autoinmune y presentación clínica heterogénea que se fundamenta en la pérdida de la tolerancia a los antígenos propios del organismo, un desorden en el sistema inmunológico y la inflamación, que conforman la base de la afectación multiorgánica crónica, así como su severidad. (2,3,4) Se ha determinado que la etnia, el sexo y la edad son factores directos implicados en la evolución y tratamiento del LES, la edad estimada de diagnóstico se encuentra entre los 35 años, (3) y se conoce que afecta primordialmente al sexo femenino hasta nueve veces más que al masculino. (3,5) La incidencia de esta enfermedad se ha cuantificado en 0,3 a 31,5 casos por 100 000 individuos y una prevalencia de 3,2 a 517,5 casos por 100 000 individuos en la población mundial.…”
Section: Introductionunclassified
“…This is evidenced by high heritability (∼66%), familial clustering (sibling recurrence risk ratio ∼30), twin studies (∼10 times higher concordance rate in monozygotic versus dizygotic twins) ( Deapen et al, 1992 ; Block, 2006 ; Mak and Tay, 2014 ; Kuo et al, 2015 ), and by a growing number of susceptibility loci identified by genome-wide association studies (GWAS) and high-density candidate gene studies [e.g., ImmunoChip ( Cortes and Brown, 2011 )]. Despite the identification of ∼180 SLE susceptibility loci ( Bentham et al, 2015 ; Sun et al, 2016 ; Langefeld et al, 2017 ; Molineros et al, 2017 ; Julia et al, 2018 ; Wang et al, 2018 ; Tangtanatakul et al, 2020 ; Ha et al, 2022 ), these account for only ∼30% of genetic heritability ( Yin et al, 2020 ), indicating that many genes and pathways remain incompletely mapped or even undiscovered.…”
Section: Introductionmentioning
confidence: 99%